New genera of Alleculinae (Coleoptera: Tenebrionidae: Alleculinae: Alleculini) from the Oriental Region. Part XI—Vietnalia gen. nov. - Novák, Vladimír (Zootaxa, 2021)
A new genus of Alleculinae (tribe Alleculini Laporte, 1840, subtribe Alleculina Laporte, 1840), Vietnalia gen. nov. with the species Vietnalia catcatica sp. nov. as a type species from the Oriental Region (Vietnam, Lao Cai Province), is described, illustrated and compared with similar (shape of body) genera Doranalia Novák, 2020 and Nikomenalia Dubrovina, 1975. Vietnalia catcatica gen. nov. and sp. nov. distinctly differs from Doranalia and Nikomenalia species particularly by antennomere 3 approximately as long as antennomere 4 in males and slightly longer than antennomere 4 in females, by ultimate maxillary palpomere widely triangular, transverse, strongly widened apically, female has antenna shorter than half body length, male abdomen has 6 visible ventrites, male ultimate and penultimate abdominal ventrites have impressions, male ultimate abdominal ventrite is excised in middle of apex. Male space between eyes is distinctly wider than in males of Doranalia species.